Abnormal GABA(A) receptors from the human epileptic hippocampal subiculum microtransplanted to Xenopus oocytes - Palma, Eleonora (National Academy of Sciences, 2005)
We studied the properties of GABA(A) receptors microtransplanted from the human temporal lobe epilepsy (TLE)-associated brain regions to Xenopus oocytes. Cell membranes, isolated from surgically resected brain specimens of drug-resistant TLE patients, were injected into frog oocytes, which rapidly incorporated human GABA(A) receptors, and any associated proteins, into their surface membrane. The receptors originating from different epileptic brain regions had a similar run-down but an affinity for GABA that was ≈60% lower for the subiculum receptors than for receptors issuing from the hippocampus proper or the temporal lobe neocortex. Moreover, GABA currents recorded in oocytes injected with membranes from the subiculum had a more depolarized reversal potential compared with the hippocampus proper or neocortex of the same patients. Quantitative RT-PCR analysis was performed of the GABA(A) receptor α1- to α5-, β1- to β3-, γ2- to γ3-, and δ-subunit mRNAs. The levels of expression of the α3-, α5-, and β1- to β3- subunit mRNAs are significantly higher, with the exception of γ2-subunit whose expression is lower, in subiculum compared with neocortex specimens. Our results suggest that an abnormal GABA-receptor subunit transcription in the TLE subiculum leads to the expression of GABA(A) receptors with a relatively low affinity. This abnormal behavior of the subiculum GABA(A) receptors may contribute to epileptogenesis.